Performance of packed bed reactor on the enzymatic interesterification of milk fat with soybean oil to yield structure lipids - de Paula, Ariela V. [UNESP]; Nunes, Gisele F.M.; de Castro, Heizir F.; dos Santos, Júlio C. (My University, 2018)
The interesterification reaction of milk fat with soybean oil mediated by Rhizopus oryzae lipase immobilised on a hybrid organic-inorganic support of polysiloxane-polyvinyl alcohol (SiO2-PVA) was assessed in a packed bed reactor running in continuous flow (45 °C, blend of milk fat and soybean oil 65:35%, w/w). The reactor performance was quantified for different flow rates corresponding to space times (0.5 and 4 h). For each condition, the influence of the space time on the consistency, free fatty acid and solid fat content (SFC, %) was determined. Percentages of reduction on consistency (71.2%) were obtained in relation to the initial blend (1431 ± 42 gf cm−2) and the SFC values (SFC10 °C = 39.6%; SFC20 °C = 20.5% and SFC35 °C = 0.2%) were within the ranges considered ideal for spreads with satisfactory spreadability. The immobilised lipase was stable with respect to its catalytic characteristics, exhibiting a half-life of 39 days.